Tosan Aji Sebagai Matakuliah Pilihan dan Kemungkinan Perkembangannya dalam Jaringan Profesi Kriya - Bagyo Suharyono (Ornamen, 2006)
Tosan Aji is type of metal handicraft that uses to make Indonesia custom weapon, example creese, sword, the spear stiletto knife, dagger, rencong (Acehnese dagger, mandau, kudi,, kujang, cleaver, chopping knife, and the other custom weapon. Characteristic Tosan Aji is the making process of pamor which found on blade of weapon. The meaning of Tosan Aji is valuable iron and respected or even sacred. The past society very respects with custom weapon specially creese and assume it will bring magic powerKeyword: Tosan Aji, pamor, blade